Market Capitalization And Trading Volume Activity Before And After Boycott Movement: Evidence From Pt. Unilever Indonesia Tbk - Mohammad Hamim Sultoni; Faiqur Rohman Nafisy; Wasilul Chair; Fahrurrozi; Lukmanul Hakim; Ishfaq Ahmed (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
This study aims to analyze Muslim Customer Behavior through Market Capitalization and Trading Volume Activity before and after the Indonesian Council of Ulama passed Fatwa (religious decree) No. 83 of 2023. This study uses a comparative descriptive quantitative approach using secondary data to examine market capitalization, stock prices per share, trading volume, and the number of shares outstanding of PT. Unilever Indonesia, Tbk. The unit analysis is the trading day and using event study to measure market capitalization and trading volume activity indicators in the stock trading period 40 days before (11 Sept 2023 until 06 Nov 2023) and 40 days after (09 Nov 2023 until 08 Jan 2024) the issuance of Indonesian Council of Ulama fatwa No.83 of 2023 on November 8, 2023. This study using normality test and wilcoxon test. The results of the study show there is a significant difference in the form of a decrease in market capitalization and trading volume activity before and after boycott movement. This decline is the effect of the market reaction to the movement not to buy certain products, resulting in product distribution being hampered, sales activities slowing down, and the company's stock market value plummeting. Analysis of events related to market capitalization and trading volume activity can be a reference for companies in acting to overcome the decline in capital market response.